2021
DOI: 10.1002/cbdv.202100404
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advance on Chemistry and Bioactivities of Secondary Metabolites from Viburnum Plants: An Update

Abstract: Viburnum species are a group of small trees or shrubs that are of great ornamental and medicinal values. Some of them have been used for a long time both as conventional and ethnic medicine. Viburnum fruits, eaten in fresh and processed forms, have been revealed to contain various health‐promoting nutrients. With the increasing research on Viburnum plants, they are considered to be an abundant resource of bioactive natural products possessing diverse pharmacological properties and unique chemical structures, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The genus Viburnum, belonging to the Adoxaceae family, consists of approximately 230 species, which are mainly distributed in warm temperate and subtropical zones. [1] Most Viburnum plants, widely used in the food and medicine fields, have gained great attention due to numerous secondary metabolites, such as terpenoids and polyphenols. These compounds possessed multiple bioactivities, including antitumor, antihyperglycemic, antioxidant, anti-inflammatory, and neuroprotective effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Viburnum, belonging to the Adoxaceae family, consists of approximately 230 species, which are mainly distributed in warm temperate and subtropical zones. [1] Most Viburnum plants, widely used in the food and medicine fields, have gained great attention due to numerous secondary metabolites, such as terpenoids and polyphenols. These compounds possessed multiple bioactivities, including antitumor, antihyperglycemic, antioxidant, anti-inflammatory, and neuroprotective effects.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds possessed multiple bioactivities, including antitumor, antihyperglycemic, antioxidant, anti-inflammatory, and neuroprotective effects. [1,2] Our previous study revealed that polyphenols form Viburnum plants exhibited significant positive effect on type 2 diabetes (T2D) by inhibiting several enzymes related to diabetes, such as α-amylase and α-glucosidase. [3] As a Chinese folk medicine, the leaves, branches, and stems of Viburnum luzonicum have been widely used to dispel wind-dampness and relieve pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010 and 2012, Fukuyama and Williams made a review, respectively, [11,12] which mainly focused on structural diversity and synthesis vibsane‐type diterpenoids. In 2021, Zhao group [13] made a review about the recent advances of Viburnum Plants. It summarized 185 new and 228 known secondary metabolites from Viburnum genus and described bioactivities and corresponding structure‐activity relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Vibsane-type diterpenoids (VibDs), a class of structurally fascinating and biologically significant secondary metabolites, were discovered exclusively in six species of the genus Viburnum (Adoxaceae) which is composed of approximately 200 species thus far. 1–3 Structurally, VibDs are generally categorized into three subtypes: 11-membered ring type (EMT), consisting of a humulane skeleton with a C 5 unit at C-11 to generate the basic scaffold of VibDs; 7-membered ring type (SMT), formed via Cope rearrangement of the EMT to possess fundamentally two ketocarbonyl groups and an isoprene unit; and rearranged ring type (RT), characterized by a C 5 unit-substituted cyclohexene ring, which is also derived from the EMT through a series of rearrangement and addition reactions. 4,5 In 2014, two tetranor-SMT diterpenoids, vibsatins A and B (Fig.…”
Section: Introductionmentioning
confidence: 99%